If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -1x) + u = 22 + 2x (3 * 4 + -1x * 4) + u = 22 + 2x (12 + -4x) + u = 22 + 2x Reorder the terms: 12 + u + -4x = 22 + 2x Solving 12 + u + -4x = 22 + 2x Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + u + -12 + -4x = 22 + -12 + 2x Reorder the terms: 12 + -12 + u + -4x = 22 + -12 + 2x Combine like terms: 12 + -12 = 0 0 + u + -4x = 22 + -12 + 2x u + -4x = 22 + -12 + 2x Combine like terms: 22 + -12 = 10 u + -4x = 10 + 2x Add '4x' to each side of the equation. u + -4x + 4x = 10 + 2x + 4x Combine like terms: -4x + 4x = 0 u + 0 = 10 + 2x + 4x u = 10 + 2x + 4x Combine like terms: 2x + 4x = 6x u = 10 + 6x Simplifying u = 10 + 6x
| 16=-8+-9y | | 7a-7b=15whatisA-B | | 3/4K-6=2k+5 | | -36a^5b^4/16a^-5b^2 | | Thiswebsiteusescookiestoensureyougetthebestexperienceonourwebsite.Moreinfo5x^2+7=9x/2 | | 15p-30= | | -10x=-24 | | 8-4/x-2=-1/2 | | x+12x=-32 | | 11r=13-2 | | -15x+54=0 | | -3n+2=0 | | 2/5r=13-4r2 | | 1/12m−1/6=1/4m+12 | | t-79=184 | | 8p+10=-4+6 | | 3/4x^2-7x+9 | | -2+8y=-6 | | 15a/25a | | (x+3)(4x-16)=0 | | 2/5h-7=13 | | Y=-2x^2-12x-23 | | 1.875=5/8(b-5) | | 12x+16=31 | | b/3=3 | | u/8=2 | | 6(y-3)=2(19-y) | | c-9=3/4c | | t/4=32 | | 2y-(13-2y)=59 | | (x+2)+y= | | 6r+4s= |